Pengembangan Bahan Ajar Menulis Cerpen dengan Media Storyboard pada Siswa Kelas X SMA - Umi Khulsum; Yusak Hudiyono; Endang Dwi Sulistyowati (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2018)
This study was conducted with the aims of (1) developing teaching materials to write short with storyboard media on high school students; (2) make a lesson plan of writing short story with storyboard media at grade X of high school students; (3) implementation of writing short story with storyboard media at rade X of high school students; (4) knowing the effectiveness of teaching materials in writing short story by using storyboard media at grade X of high school students. This study need a development research method adapted from the Borg and Gall development model with 10 stages beginning with needs analysis, planning, initial product development, initial product revision, product trial, product revision, small field trial, revision product, operational field test (large group), final product revision, and product dissemination and implementation. Based on the data analysis, it was concluded that the teaching materials to write short story with the developed storyboard media was considered feasible and effective to be used as teaching materials for Bahasa Indonesia at Grade X of high school students.